G12 What are the Research Priorities of Paediatric Emergency Medicine Clinicians in the United Kingdom & Ireland? An International Survey. (7th April 2014) - Hartshorn, S; Bevan, C; Cleugh, F; Lyttle, M; Maconochie, I; O'Sullivan, R
Abstract : Aims: Paediatric Emergency Research in the UK and Ireland (PERUKI) is a research collaborative that was established in August 2012. It consists of 40 centres from England, Ireland, Northern Ireland, Scotland and Wales, and aims to improve the emergency care of children through the performance of robust collaborative multicentre research within Emergency Departments (EDs). A study was conducted to establish the research priorities of PERUKI, in order to direct potential projects and to share these priorities with funding agencies to inform future calls for study proposals. Methods: A 2-stage modified Delphi survey was conducted of all PERUKI members via an online survey platform. Round 1 allowed each member to submit up to 12 individual questions in "PICO" format that they identified as priorities for future research. From this total bank of responses, a list of all unique research questions was compiled, grouped by subject area/topic. A shortlist of eligible questions was then drawn up by the PERUKI Executive Committee during a teleconference analysis discussion. Questions were considered to be eligible for further consideration if they were unanswered in the current literature and if they leant themselves to multi-centre research within EDs. In Round 2, members reviewed each of the shortlisted questions and rated each on a 7-point Likert scale of relative importance to clinical practice in Paediatric Emergency Medicine. Questions were then ranked according to total priority score. Results: Round 1: Response rate = 46/91 (51%) Round 2: Response rate = 58/95 (61%) After ranking, the top 10 priorities included questions on biomarkers for serious bacterial illness, major trauma, intravenous bronchodilators for asthma, and decision rules for fever with petechiae, head injury and atraumatic limp. Conclusion: Research priorities of PERUKI members have been identified. We are dovetailing this with the next step of identifying relevant funding bodies to progress research in these areas of Paediatric Emergency Medicine.